2022
DOI: 10.29040/jiei.v8i3.6837
|View full text |Cite
|
Sign up to set email alerts
|

Deteksi Minat Menabung Di Bank Syariah : Suatu Kajian Empiris

Ardiani Ika Sulistyawati,
Yuntika L.E. Dini,
Dian Triyani
et al.

Abstract: The purpose of this research is to analyze the factors that influence the interest in saving in Islamic banks. The object of research at the University of Semarang with the unit of analysis is students of the accounting study program. The number of respondents who participated were 84 people. This type of research is included as quantitative research. The analysis technique to answer the hypothesis uses multiple linear regression models. Data analysis was carried out using the SPSS'25 program. The results of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Minat bisa diartikan sebagai sebuah dorongan seseorang untuk melakukan yang diinginkan, setiap minat akan memutuskan suatu kebutuhan (Sulistyawati, Dini, Triyani, & Prapti, 2022). Minat menabung adalah dorongan yang menyebabkan seseorang menyimpan uangnya di bank yang penarikannya hanya dapat dilakukan menurut syarat-syarat tertentu yang telah disepakati antara bank dengan nasabah (Nengsih, Arsa, & Putri, 2021).…”
Section: Minat Menabungunclassified
“…Minat bisa diartikan sebagai sebuah dorongan seseorang untuk melakukan yang diinginkan, setiap minat akan memutuskan suatu kebutuhan (Sulistyawati, Dini, Triyani, & Prapti, 2022). Minat menabung adalah dorongan yang menyebabkan seseorang menyimpan uangnya di bank yang penarikannya hanya dapat dilakukan menurut syarat-syarat tertentu yang telah disepakati antara bank dengan nasabah (Nengsih, Arsa, & Putri, 2021).…”
Section: Minat Menabungunclassified
“…Previous research has uncovered inconsistencies that serve as the empirical foundation for the significance of this research. Various prior studies have indicated that religiosity is a key determinant of individuals' interest in saving in Islamic banks (Mardiana et al, 2021;Sodik et al, 2022;Sulistyawati et al, 2022). In addition to religiosity, financial literacy has recently gained recognition as a critical determinant of interest in saving in Islamic banks (Afriani & Asandimitra,…”
mentioning
confidence: 99%